设A,B为两个事件,P(A)=0.9,P(AB)=0.36,则P(A-B)= .
0.54
举一反三
- 设A和B是两事件,A包含B,P(A)=0.9,P(B)=0.36,则P(A-B)=( ) A: 0.1 B: 0.64 C: 0.54 D: 0.9
- 设A、B为两个随机事件,P(A)=0.8,P(AB)=0.4,则P(A-B)=()。
- 设A、B为两个随机事件,则P(A-B)=( ) A: P B: -P C: -P(AB) D: +P
- 设A、B为两事件,则P(A-B)=( ) A: P(A)-P(AB) B: P(A)-P(B)+P(AB) C: P(A)-P(B) D: P(A)+P(B)-P(AB)
- 设A,B是任意两个随机事件,则P(A-B)=( ) A: P(A)-P(B) B: P(A)-P(B)+P(AB) C: P(A)-P(AB) D: P(A)+P(B)-P(AB)
内容
- 0
设A,B是两个随机事件,则P(A-B)= 未知类型:{'options': ['P(A)-P(B)', 'P(A)-P(B)+P(AB)', 'P(A)-P(AB)', ''], 'type': 102}
- 1
设A,B为随机事件,则P(A-B)= A: P(A)-P(B) B: P(A)-P(AB) C: P(A)-P(B)+ P(AB) D: P(A)+P(B)- P(AB)
- 2
设A与B是两个随机事件,则P(A-B)= A: P(A) B: P(B) C: P(A)-P(B) D: P(A)-P(AB)
- 3
设A和B为两个随机事件,且P(A)=0.8,P(B)=0.4,则P(A-B)=()设A和B为两个随机事件,且P(A)=0.8,P(B)=0.4,则P(A-B)=()
- 4
设A,B是两个随机事件,则P(A-B)= A: P(A)-P(B) B: P(A)-P(B)+P(AB) C: P(A)-P(AB) D: [img=167x27]180378d6b184355.png[/img]